Bioprospecting of bacterial symbionts of sponge Spongia officinalis from Savu Sea, Indonesia for antibacterial potential against multidrug-resistant bacteria - MUHAMMAD EVY PRASTIYANTO; APRILIA INDRA KARTIKA; SRI DARMAWATI; OCKY KARNA RADJASA (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Prastiyanto ME, Kartika AI, Darmawati S, Radjasa OK. 2022. Bioprospecting of bacterial symbionts of sponge Spongia officinalis from Savu Sea, East Nusa Tenggara, Indonesia for antibacterial potential against multidrug-resistant bacteria. Biodiversitas 23: 1118-1124. Marine sponge Spongia sp. has been reported to have potential as an antibacterial agent. However, less information on the potential of bacterial symbionts of Spongia sp. as an antibacterial agent has been documented. The present investigation involves isolating bacterial symbionts of sponge Spongia officinalis and the characterization of antibacterial potential against multidrug-resistant bacteria isolated from clinical specimens. Spongia officinalis was collected from Savu Sea, East Nusa Tenggara, Indonesia and its symbionts were isolated with Zobell marine agar media. The overlay method was used to screen the antibacterial activity against selected six MDR bacteria. Antibacterial activity was determined by measuring the diameter of the inhibition zone. Identification of active bacterial symbionts was carried out based on the 16S rRNA gene sequencing. The results revealed that four out of 10 symbionts showed antibacterial activity against MDR bacteria with an inhibition index ranging from 4.8 to 12.6 mm. Prastiyanto-1A and Prastiyanto-1E isolates demonstrated antibacterial activity against ESBL- Escherichia coli and ESBL + CRE- Klebsiella pneumoniae subsp. pneumoniae, Pratiyanto-2A isolate showed antibacterial activity against MRSA, while Prastiyanto-4A isolates showed antibacterial activity against CRPA. The selected four isolates were identified as Bacillus subtilis, Bacillus mojavensis and Bacillus simplex using 16S rRNA gene sequencing and BLASTn analysis. These results provide information about the potential of bacterial symbionts of S. officinalis as natural antibacterial sources against MDR bacteria.